2020
DOI: 10.1021/acs.jmedchem.0c00415
|View full text |Cite
|
Sign up to set email alerts
|

Essential Medicinal Chemistry of Essential Medicines

Abstract: Since 1977, the World Health Organization publishes a list of essential medicines, i.e., those that satisfy the priority health care needs of the population and are selected with regard to disease prevalence and public health relevance, evidence of clinical efficacy, and safety, as well as comparative costs and cost-effectiveness. The Essential Medicines List (EML) is an invaluable tool for all countries to select those medicines that have an excellent risk/benefit ratio and that are reputed to be of pivotal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 69 publications
0
16
0
2
Order By: Relevance
“…Many methods have been reported for the synthesis of “C-CF 2 -C”-containing molecules . However, direct introduction of the CF 2 unit into a stereogenic carbon (C*) to provide chiral gem -difluoromethylene compounds with a “C-CF 2 -C*” unit has remained a challenge, despite the growing requirement from the global chiral chemicals market . In 2014, we reported the first enantioselective allylic trifluoromethylation of Morita–Baylis–Hillman (MBH) fluorides by (tri­fluoro­methyl)­trimethylsilane (CF 3 SiMe 3 , Ruppert–Prakash reagent) under metal-free cinchona alkaloid catalysis .…”
mentioning
confidence: 99%
“…Many methods have been reported for the synthesis of “C-CF 2 -C”-containing molecules . However, direct introduction of the CF 2 unit into a stereogenic carbon (C*) to provide chiral gem -difluoromethylene compounds with a “C-CF 2 -C*” unit has remained a challenge, despite the growing requirement from the global chiral chemicals market . In 2014, we reported the first enantioselective allylic trifluoromethylation of Morita–Baylis–Hillman (MBH) fluorides by (tri­fluoro­methyl)­trimethylsilane (CF 3 SiMe 3 , Ruppert–Prakash reagent) under metal-free cinchona alkaloid catalysis .…”
mentioning
confidence: 99%
“…There have been many biological investigations related to pyrazine- and phenazine-containing compounds that demonstrate therapeutic value related to human health and disease. The World Health Organization’s (WHO) Model List of Essential Medicines in 2019 included four pyrazine (amiloride, bortezomib, paritaprevir, pyrazinamide) and one phenazine (clofazimine) drug molecules [ 7 ]. The pyrazine scaffold offers additional promise, as computational studies have shown common drug–target interactions related to biologically active pyrazines, lending credence to incorporating this heterocycle, along with phenazine, into appropriate drug design campaigns [ 8 ].…”
Section: Pyrazines and Phenazines Of Therapeutic Interestmentioning
confidence: 99%
“…Clofazimine is often administered in combination with rifampin and/or dapsone due to the high frequency of resistance that many leprosy infections have to these antibiotics [ 30 ]. In addition, clofazimine is on the World Health Organization’s (WHO) model list of essential medicines, illustrating its global therapeutic impact [ 7 ].…”
Section: Pyrazines and Phenazines Of Therapeutic Interestmentioning
confidence: 99%
“…In our opinion, the pINN and rINN publications are a unique opportunity to scrutinize drug development as well as the recent trends in drug research and development (R&D) (as they precede marketing by a few years, see below), and, to our knowledge, this has been overlooked by scholars. Moreover, the INN publications have never been scrutinized from a medicinal chemistry viewpoint, unlike other chemical catalogues, such as FDA-approved drugs, including veterinary drugs, the Essential Medicines List (EML), or molecules published in medicinal chemistry journals. , In the present contribution, we concentrated on the chemical entities published in the INN lists in this millennium. Indeed, the publication of the INN represents at times the first public disclosure of the molecule and, while obviously not all substances that have been assigned an INN turn into approved drugs, these are all compounds that the industry has invested in.…”
Section: Introductionmentioning
confidence: 99%